Near-Complete Supraglottic Transection of the Larynx after a Motorbike Accident - Sang Hwang; Samuel McGinness; Sim Choroomi; Ian Jacobson (Case Reports in Otolaryngology)
Severe laryngeal trauma is rare in the civilian environment and requires appropriate and timely surgical intervention. We report a case from Sydney, Australia, which was managed with open reduction and internal fixation of the larynx with resorbable plates. The use of resorbable plates for operative fixation of the larynx has rarely been reported in literature but may be a viable alternative.